UHPC lightweight plate prepared based on limestone mechanism sand and preparation method thereof

CN119349956BActive Publication Date: 2026-10-30GUANGXI ZHUANG AUTONOMOUS REGION CONSTR ENG QUALITY INSPECTION CENT CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411524800.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2026-10-30
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

[0004]现有技术是通过调整UHPC的配方来提高其抗温差性能,例如增加纤维含量或使用特殊添加剂来提高抗裂性能,但是增加纤维含量会导致板材的强度降低,不能满足现有市场的需求

Benefits of technology

[0036]1、本发明通过对硅锰渣、磷渣粉这两种物质分别进行改性,可以改善板材的抗压强度,通过有机盐进行改性,可以起到化学激发作用,能够改善混凝土拌合物的工作性能,调整混凝土拌合物的状态。本发明采用陶粒代部分骨料作为内养护骨料,一是内养护骨料可以储存水分,在养护阶段不断释放水分给水泥水化用,促进水泥水化程度,提高基材强度;二是陶粒是轻骨料,可以制备密度较轻的轻量化板。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005108925850000121
    Figure BDA0005108925850000121
  • Figure BDA0005108925850000131
    Figure BDA0005108925850000131
Patent Text Reader

Abstract

The application provides a UHPC light-weight plate prepared based on limestone machine-made sand and a preparation method thereof, the UHPC light-weight plate comprises the following raw materials in parts by weight: 22-27 parts of ceramsite, 12-15 parts of steel fiber, 420-460 parts of ordinary cement, 40-50 parts of modified silicon-manganese slag, 15-27 parts of modified phosphorous slag powder, 50-70 parts of limestone particles, 10-18 parts of steel slag, 20-40 parts of fly ash, 40-60 parts of mineral powder, 400-420 parts of limestone machine-made sand, 6-10 parts of polycarboxylic acid water reducing agent, 0.2-0.4 parts of hydroxyethyl methyl cellulose and 150-170 parts of water. The UHPC light-weight plate prepared based on limestone machine-made sand has excellent mechanical properties, good temperature resistance and strong impact resistance, and has wide market prospect and application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of building technology, specifically relating to a UHPC lightweight board based on limestone manufactured sand and its preparation method. Background Technology

[0002] UHPC, or Ultra-High Performance Concrete, is a new type of high-performance building material. Due to its superior mechanical properties and durability, it has been widely used in engineering fields such as construction, bridges, and roads. UHPC panels, as an important application of UHPC, possess numerous advantages such as lightweight, high strength, durability, fire resistance, and thermal insulation.

[0003] When using ultra-high performance concrete (UHPC) panels in areas with large temperature differences, some specific technical problems arise that affect the material's performance: (1) Temperature stress: In environments with large temperature differences, UHPC panels may experience significant temperature changes, resulting in temperature stress. Excessive temperature stress may cause microcracks to form inside the material, thereby affecting the integrity and durability of the overall structure. (2) Thermal expansion and contraction: UHPC is also affected by thermal expansion and contraction, especially in areas with large diurnal temperature differences or significant seasonal changes. If the design and construction are not done properly, this physical change may lead to structural deformation or cracking. (3) Shrinkage cracks: UHPC undergoes a certain degree of shrinkage during the hardening process, and in environments with large temperature differences, this shrinkage effect may be amplified, leading to cracks on the surface or inside the panel.

[0004] Existing technologies improve the temperature resistance of UHPC by adjusting its formulation, such as increasing fiber content or using special additives to improve crack resistance. However, increasing fiber content leads to a decrease in the strength of the board, which cannot meet the needs of the current market.

[0005] Therefore, there is an urgent need for a lightweight UHPC sheet material with good temperature resistance and high mechanical strength. Summary of the Invention

[0006] The purpose of this invention is to provide a lightweight UHPC slab based on limestone manufactured sand and its preparation method. The addition of ceramsite as an internal curing component provides moisture for the internal hydration of the UHPC, increasing the hydration rate and hardened body strength, and reducing early cracking and self-shrinkage.

[0007] To achieve the above objectives, the present invention provides the following technical solution:

[0008] A lightweight UHPC board based on limestone manufactured sand comprises the following raw materials in parts by weight: 22-27 parts ceramsite, 12-15 parts steel fiber, 420-460 parts ordinary cement, 40-50 parts modified ferrosilicon manganese slag, 15-27 parts modified phosphorus slag powder, 50-70 parts limestone particles, 10-18 parts steel slag, 20-40 parts fly ash, 40-60 parts mineral powder, 400-420 parts limestone manufactured sand, 6-10 parts polycarboxylate superplasticizer, 0.2-0.4 parts hydroxyethyl methyl cellulose, and 150-170 parts water.

[0009] Furthermore, the preparation method of modified ferromanganese slag includes: mixing 100 parts by weight of ferromanganese slag powder with 0.2-0.4 parts by weight of tartrate and 0.1-0.3 parts by weight of sodium p-aminobenzenesulfonate to obtain modified ferromanganese slag powder.

[0010] Furthermore, the preparation method of modified phosphorus slag powder includes: mixing 100 parts by weight of phosphorus slag powder, 0.3-0.6 parts by weight of quaternary ammonium salt cationic starch and 0.2-0.4 parts by weight of sodium citrate evenly to obtain modified phosphorus slag powder.

[0011] The method for preparing the ceramsite includes the following steps:

[0012] (1) Material preparation: crush, grind and screen the coal gangue to obtain coal gangue powder with a particle size of 0.1-0.15mm;

[0013] (2) Mixing: Weigh the raw materials according to the following weight ratio: 12-15% clay powder, 7-12% shale powder, 2-5% mineral powder, and the remainder coal gangue powder; mix the raw materials evenly to obtain a mixed powder; add 20-24% of the total weight of the mixed powder to the mixed powder, stir, and let stand to obtain the mixed powder.

[0014] (3) Granulation: The mixture is extruded into strips, then dried, crushed and passed through a 100-mesh sieve to obtain dried granules;

[0015] (4) Calcination: The dried particles are calcined at 1050-1100℃ for 35-40 minutes and then naturally cooled to room temperature to obtain ceramsite.

[0016] This invention attempts to improve the compressive strength of slabs by adding phosphorus slag powder and manganese silicon slag, but the effect is not ideal, mainly because the active substances cannot be well activated in the system, resulting in poor performance. This invention improves the compressive strength of slabs by modifying these two substances separately. Modification with organic salts can chemically activate the mixture, improving its workability and adjusting its state. Chloride ions can penetrate the slab and corrode its internal structure, affecting its durability; therefore, the slab's resistance to chloride ion penetration is crucial. Adding specific amounts of modified manganese silicon slag and modified phosphorus slag powder to the system of this invention improves the slab's resistance to chloride ion penetration. Analysis shows that under these conditions, the slab's structural density increases, the overall electrical flux is low, the resistance to chloride ion penetration is good, and the product has good durability. However, after adding modified manganese silicon slag and modified phosphorus slag powder, the slab's temperature resistance is not ideal, especially under impact conditions where cracking is likely.

[0017] Furthermore, the ordinary cement is a mixture of P.O42.5 ordinary Portland cement and P.O52.5 ordinary Portland cement in a weight ratio of (2-4):1.

[0018] Furthermore, the preparation method of the polycarboxylate superplasticizer includes:

[0019] (1) Mix 70-80 parts by weight of microcrystalline cellulose and 20-30 parts by weight of unsaturated monomer, treat with microwave assistance, add 1-3 parts by weight of p-toluenesulfonic acid and 0.03-0.05 parts by weight of hydroquinone, stir and heat to 80-100℃ for 5-8 hours to obtain the first monomer;

[0020] (2) Add 30-40 parts by weight of silane coupling agent KH550 dropwise to 60-70 parts by weight of unsaturated carboxylic acid, add 1-3 parts by weight of p-toluenesulfonic acid and 0.03-0.05 parts by weight of hydroquinone, react at 60-70℃ for 2-3 hours to obtain the second monomer.

[0021] (3) Mix 30-40 parts by weight of the first monomer, 60-70 parts by weight of the second monomer and 200-250 parts by weight of water, heat to 60-80℃, and add 15-20 parts by weight of maleic anhydride, 1-2 parts by weight of ammonium persulfate and 1-2 parts by weight of isopropanol dropwise over 1-2 hours. After reacting for 2-7 hours, stop heating to obtain the copolymer.

[0022] (4) Add sodium hydroxide solution to the copolymer to adjust the pH to 5-5.5, and dilute with water to a mass fraction of 22-26% to obtain polycarboxylate superplasticizer.

[0023] Microcrystalline cellulose was purchased from Hunan Yunbang Biotechnology Co., Ltd., product number: YM59139.

[0024] Furthermore, the unsaturated monomer is a mixture of methacrylic acid, acrylic acid and maleic anhydride in a weight ratio of 1:(1.3-1.7):(0.2-0.5).

[0025] Furthermore, the unsaturated carboxylic acid is methacrylic acid, acrylic acid and maleic acid in a weight ratio of (1.6-1.8):1:(0.4-0.7).

[0026] The commercially available polycarboxylate superplasticizers used in this invention do not provide ideal improvements to the temperature resistance of the boards. The polycarboxylate superplasticizer prepared in this invention can effectively improve the temperature resistance of the boards, especially their impact resistance under varying temperature conditions. The polycarboxylate superplasticizer of this invention contains cellulose groups; the microcrystalline cellulose groups help improve the microstructure of concrete and reduce porosity. This helps increase the density of the concrete. The microcrystalline cellulose groups can improve the interfacial bonding between the components within the concrete, improving the overall integrity of the concrete. Furthermore, modification with the silane coupling agent KH550 improves interfacial bonding, reducing the occurrence of microcracks in the interfacial region caused by temperature changes and improving the impact resistance of the concrete. This invention uses unsaturated monomers and unsaturated carboxylic acids in a specific ratio and composition, giving the polycarboxylate superplasticizer a unique network structure. This promotes the close arrangement of particles within the concrete, increasing the overall density of the concrete and further enhancing its resistance to temperature changes. It can also improve the flexural strength of the boards.

[0027] Furthermore, hydroxyethyl methylcellulose is EASONZELL TM ME4000. Purchased from Zhejiang Yisheng New Materials Co., Ltd.

[0028] Furthermore, the manufactured limestone sand comprises 20-40 mesh, 40-70 mesh, and 100-130 mesh manufactured limestone sand in a weight ratio of 1:3-4:0.2-0.5.

[0029] Furthermore, the specific surface area of ​​the mineral powder is 680-770 m². 2 / kg.

[0030] This invention also provides a method for preparing UHPC lightweight panels based on limestone manufactured sand, the method comprising the following steps:

[0031] (1) Weigh the raw materials according to the weight ratio, mix them evenly, and inject them into the mold for vibration molding;

[0032] (2) Place the molded board in a flat, quiet resting area and let it stand for 4-6 hours for initial setting. The temperature of the initial setting room is 20℃ and the relative humidity is 65-75%.

[0033] (3) After the initial curing is completed, the mold is removed and moved to the final curing chamber for steam curing. The temperature of the final curing chamber is controlled at 75-85℃ and the curing time is 45-55h.

[0034] (4) After the final curing is completed, the material is removed from the final curing room and cured by watering for 17-20 days to obtain UHPC lightweight boards based on limestone manufactured sand.

[0035] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows:

[0036] 1. This invention improves the compressive strength of the board by modifying ferrosilicon manganese slag and phosphorus slag powder separately. Modification with organic salts provides chemical activation, improving the workability and adjusting the state of the concrete mixture. This invention uses expanded clay aggregate as part of the internal curing aggregate. Firstly, the internal curing aggregate can store moisture and continuously release it during the curing stage for cement hydration, promoting the degree of cement hydration and increasing the strength of the substrate. Secondly, expanded clay aggregate is a lightweight aggregate, enabling the preparation of lightweight boards with lower density.

[0037] 2. Adding specific amounts of modified ferrosilicon manganese slag and modified phosphorus slag powder to the system of the present invention can improve the resistance of the board to chloride ion penetration.

[0038] 3. The polycarboxylate superplasticizer prepared by this invention can effectively improve the temperature resistance of the board, especially its impact resistance under varying temperature conditions. It can also improve the flexural strength of the board. Detailed Implementation

[0039] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0040] The raw materials used in this invention were purchased from the following manufacturers:

[0041] Silicon manganese slag powder, Qinghe County Xingxin New Material Technology Co., Ltd., 300-500 mesh.

[0042] Phosphorus slag, Shijiazhuang Yuanjing Mineral Products Co., Ltd., 500-1000 mesh.

[0043] Limestone particles, Guangxi Runhan New Material Technology Co., Ltd., 1000-2000 mesh.

[0044] Steel slag, Guangxi Yuansheng Slag Comprehensive Utilization Co., Ltd., 500-2000 mesh.

[0045] Fly ash, Guangxi Qinzhou Landao Environmental Protection Materials Co., Ltd., 200-600 mesh.

[0046] Mineral powder, Guangxi Yuansheng Slag Comprehensive Utilization Co., Ltd., S95 mineral powder.

[0047] Steel fiber, Shandong Hongshuo New Material Co., Ltd., sheared steel fiber.

[0048] Manufactured limestone sand, Guangxi Runhan New Material Technology Co., Ltd., fineness modulus 2.4-2.9.

[0049] Clay powder: Calcined kaolin clay powder, Lingshou County Anda Mineral Powder Factory, average particle size 1250 mesh.

[0050] Example 1

[0051] This embodiment provides a UHPC lightweight board based on limestone manufactured sand, comprising the following raw materials by weight: 24 parts ceramsite, 13 parts steel fiber, 440 parts ordinary cement, 45 parts modified ferrosilicon manganese slag, 21 parts modified phosphorus slag powder, 60 parts limestone particles, 15 parts steel slag, 27 parts fly ash, 49 parts mineral powder, 410 parts limestone manufactured sand, 8 parts polycarboxylate superplasticizer, 0.3 parts hydroxyethyl methyl cellulose, and 160 parts water.

[0052] The preparation method of modified ferrosilicon slag includes: mixing 100 parts by weight of ferrosilicon slag powder, 0.3 parts by weight of tartrate and 0.2 parts by weight of sodium p-aminobenzenesulfonate evenly to obtain modified ferrosilicon slag powder.

[0053] The preparation method of modified phosphorus slag powder includes: mixing 100 parts by weight of phosphorus slag powder, 0.5 parts by weight of quaternary ammonium salt cationic starch and 0.3 parts by weight of sodium citrate evenly to obtain modified phosphorus slag powder.

[0054] The method for preparing the ceramsite includes the following steps:

[0055] (1) Material preparation: crush, grind and screen the coal gangue to obtain coal gangue powder with a particle size between 0.1-0.15mm;

[0056] (2) Mixing: Weigh the raw materials according to the following weight ratio: 13% clay powder, 9% shale powder, 4% mineral powder, and the remainder coal gangue powder; mix the raw materials evenly to obtain a mixed powder; add 22% of the total weight of the mixed powder to the mixed powder, stir, and let stand to obtain a mixed powder.

[0057] (3) Granulation: The mixture is extruded into strips, then dried, crushed and passed through a 100-mesh sieve to obtain dried granules;

[0058] (4) Calcination: The dried particles are calcined at 1060℃ for 38 minutes and then naturally cooled to room temperature to obtain ceramsite.

[0059] The ordinary cement is a mixture of P.O42.5 ordinary Portland cement and P.O52.5 ordinary Portland cement in a weight ratio of 3:1.

[0060] The preparation method of the polycarboxylate superplasticizer includes:

[0061] (1) Mix 75 parts by weight of microcrystalline cellulose and 25 parts by weight of unsaturated monomer, and after microwave-assisted treatment, add 2 parts by weight of p-toluenesulfonic acid and 0.04 parts by weight of hydroquinone, stir and heat to 90°C for 6 hours to obtain the first monomer; the unsaturated monomer is a mixture of methacrylic acid, acrylic acid and maleic anhydride in a weight ratio of 1:1.5:0.4.

[0062] (2) 35 parts by weight of silane coupling agent KH550 were added dropwise to 66 parts by weight of unsaturated carboxylic acid, 2 parts by weight of p-toluenesulfonic acid and 0.04 parts by weight of hydroquinone were added, and the reaction was carried out at 65°C for 2.5 h to obtain the second monomer; the unsaturated carboxylic acid was methacrylic acid, acrylic acid and maleic acid in a weight ratio of 1.7:1:0.6.

[0063] (3) Mix 35 parts by weight of the first monomer, 65 parts by weight of the second monomer and 230 parts by weight of water, heat to 70°C, and add 17 parts by weight of maleic anhydride, 1.5 parts by weight of ammonium persulfate and 1.6 parts by weight of isopropanol dropwise over 1.6 hours. After reacting for 5 hours, stop heating to obtain the copolymer.

[0064] (4) Add sodium hydroxide solution to the copolymer to adjust the pH to 5.2, and dilute with water to a mass fraction of 24% to obtain polycarboxylate superplasticizer.

[0065] Microcrystalline cellulose was purchased from Hunan Yunbang Biotechnology Co., Ltd., product number: YM59139.

[0066] Hydroxyethyl methylcellulose is Easonzel TM ME4000. Purchased from Zhejiang Yisheng New Materials Co., Ltd.

[0067] The manufactured limestone sand includes 20-40 mesh, 40-70 mesh, and 100-130 mesh manufactured limestone sand in a weight ratio of 1:3.2:0.3.

[0068] The specific surface area of ​​the mineral powder is 680-770 m². 2 / kg.

[0069] The method for preparing UHPC lightweight panels based on limestone manufactured sand includes the following steps:

[0070] (1) Weigh the raw materials according to the weight ratio, mix them evenly, and inject them into the mold for vibration molding;

[0071] (2) Place the molded board in a flat, quiet resting area and let it stand for 5 hours for initial setting. The temperature of the initial setting room should be controlled at 20℃ and the relative humidity at 70%.

[0072] (3) After the initial curing is completed, the mold is removed and moved to the final curing chamber for steam curing. The temperature of the final curing chamber is controlled at 80℃ and the curing time is 48h.

[0073] (4) After the final curing is completed, the material is removed from the final curing room and cured by watering for 18 days to obtain UHPC lightweight boards based on limestone manufactured sand.

[0074] Example 2

[0075] This embodiment provides a UHPC lightweight board based on limestone manufactured sand, comprising the following raw materials by weight: 22 parts ceramsite, 15 parts steel fiber, 420 parts ordinary cement, 40 parts modified ferrosilicon manganese slag, 15 parts modified phosphorus slag powder, 50 parts limestone particles, 10 parts steel slag, 20 parts fly ash, 40 parts mineral powder, 400 parts limestone manufactured sand, 6 parts polycarboxylate superplasticizer, 0.2 parts hydroxyethyl methyl cellulose, and 150 parts water.

[0076] The preparation method of modified ferrosilicon slag includes: mixing 100 parts by weight of ferrosilicon slag powder, 0.2 parts by weight of tartrate and 0.1 parts by weight of sodium p-aminobenzenesulfonate evenly to obtain modified ferrosilicon slag powder.

[0077] The preparation method of modified phosphorus slag powder includes: mixing 100 parts by weight of phosphorus slag powder, 0.3 parts by weight of quaternary ammonium salt cationic starch and 0.2 parts by weight of sodium citrate evenly to obtain modified phosphorus slag powder.

[0078] The method for preparing the ceramsite includes the following steps:

[0079] (1) Material preparation: crush, grind and screen the coal gangue to obtain coal gangue powder with a particle size between 0.1-0.15 mm;

[0080] (2) Mixing: Weigh the raw materials according to the following weight ratio: 12% clay powder, 12% shale powder, 2% mineral powder, and the remainder coal gangue powder; mix the raw materials evenly to obtain a mixed powder; add 24% of the total weight of the mixed powder to the mixed powder, stir, and let stand to obtain a mixed powder.

[0081] (3) Granulation: The mixture is extruded into strips, then dried, crushed and passed through a 100-mesh sieve to obtain dried granules;

[0082] (4) Calcination: The dried particles are calcined at 1100℃ for 35 minutes and then naturally cooled to room temperature to obtain ceramsite.

[0083] The ordinary cement is a mixture of P.O42.5 ordinary Portland cement and P.O52.5 ordinary Portland cement in a weight ratio of 2:1.

[0084] The preparation method of the polycarboxylate superplasticizer includes:

[0085] (1) Mix 70 parts by weight of microcrystalline cellulose and 20 parts by weight of unsaturated monomer, and after microwave-assisted treatment, add 1 part by weight of p-toluenesulfonic acid and 0.03 parts by weight of hydroquinone, stir and heat to 80°C for 5 hours to obtain the first monomer; the unsaturated monomer is a mixture of methacrylic acid, acrylic acid and maleic anhydride in a weight ratio of 1:1.3:0.2.

[0086] (2) 30 parts by weight of silane coupling agent KH550 were added dropwise to 60 parts by weight of unsaturated carboxylic acid, 1 part by weight of p-toluenesulfonic acid and 0.03 parts by weight of hydroquinone were added, and the reaction was carried out at 60°C for 2 hours to obtain the second monomer; the unsaturated carboxylic acid was methacrylic acid, acrylic acid and maleic acid in a weight ratio of 1.6:1:0.4.

[0087] (3) Mix 30 parts by weight of the first monomer, 60 parts by weight of the second monomer and 200 parts by weight of water, heat to 60°C, and add 15 parts by weight of maleic anhydride, 1 part by weight of ammonium persulfate and 1 part by weight of isopropanol dropwise over 1 hour. After reacting for 2 hours, stop heating to obtain the copolymer.

[0088] (4) Add sodium hydroxide solution to the copolymer to adjust the pH to 5, and dilute with water to a mass fraction of 22% to obtain polycarboxylate superplasticizer.

[0089] Microcrystalline cellulose was purchased from Hunan Yunbang Biotechnology Co., Ltd., product number: YM59139.

[0090] Hydroxyethyl methylcellulose is Easonzel TM ME4000. Purchased from Zhejiang Yisheng New Materials Co., Ltd.

[0091] The manufactured limestone sand includes 20-40 mesh, 40-70 mesh, and 100-130 mesh manufactured limestone sand in a weight ratio of 1:3:0.2.

[0092] The specific surface area of ​​the mineral powder is 680-770 m². 2 / kg.

[0093] The method for preparing UHPC lightweight panels based on limestone manufactured sand includes the following steps:

[0094] (1) Weigh the raw materials according to the weight ratio, mix them evenly, and inject them into the mold for vibration molding;

[0095] (2) Place the molded board in a flat, quiet resting area and let it stand for 4 hours for initial setting. The temperature of the initial setting room should be controlled at 20℃ and the relative humidity at 70%.

[0096] (3) After the initial curing is completed, the mold is removed and moved to the final curing chamber for steam curing. The temperature of the final curing chamber is controlled at 80℃ and the curing time is 48h.

[0097] (4) After the final curing is completed, the material is removed from the final curing room and cured by watering for 17 days to obtain UHPC lightweight boards based on limestone manufactured sand.

[0098] Comparative Example 1

[0099] The difference between this comparative example and Example 1 is that it contains 21 parts of modified ferrosilicon manganese slag and 45 parts of modified phosphorus slag powder.

[0100] Comparative Example 2

[0101] The difference between this comparative example and Example 1 is that it contains 57 parts fly ash, 69 parts mineral powder, and 360 parts manufactured limestone sand.

[0102] Comparative Example 3

[0103] The difference between this comparative example and Example 1 is that the unsaturated monomers are a mixture of methacrylic acid, acrylic acid, and maleic anhydride in a weight ratio of 1:1:1. The unsaturated carboxylic acid is a mixture of methacrylic acid, acrylic acid, and maleic acid in a weight ratio of 1:1:1.

[0104] Comparative Example 4

[0105] The difference between this comparative example and Example 1 is that the preparation method of the polycarboxylate superplasticizer includes:

[0106] (1) Mix 75 parts by weight of microcrystalline cellulose and 25 parts by weight of unsaturated monomer, and after microwave-assisted treatment, add 2 parts by weight of p-toluenesulfonic acid and 0.04 parts by weight of hydroquinone, stir and heat to 90°C for 6 hours to obtain the first monomer; the unsaturated monomer is a mixture of methacrylic acid, acrylic acid and maleic anhydride in a weight ratio of 1:1.5:0.4.

[0107] (2) Mix 100 parts by weight of the first monomer and 230 parts by weight of water, heat to 70°C, and add 17 parts by weight of maleic anhydride, 1.5 parts by weight of ammonium persulfate and 1.6 parts by weight of isopropanol dropwise over 1.6 hours. After reacting for 5 hours, stop heating to obtain the copolymer.

[0108] (3) Add sodium hydroxide solution to the copolymer to adjust the pH to 5.2, and dilute with water to a mass fraction of 24% to obtain polycarboxylate superplasticizer.

[0109] Comparative Example 5

[0110] The difference between this comparative example and Example 1 is that the preparation method of the polycarboxylate superplasticizer includes:

[0111] (1) 35 parts by weight of silane coupling agent KH550 were added dropwise to 66 parts by weight of unsaturated carboxylic acid, 2 parts by weight of p-toluenesulfonic acid and 0.04 parts by weight of hydroquinone were added, and the reaction was carried out at 65°C for 2.5 h to obtain the first monomer; the unsaturated carboxylic acid was methacrylic acid, acrylic acid and maleic acid in a weight ratio of 1.7:1:0.6.

[0112] (2) Mix 100 parts by weight of the first monomer and 230 parts by weight of water, heat to 70°C, and add 17 parts by weight of maleic anhydride, 1.5 parts by weight of ammonium persulfate and 1.6 parts by weight of isopropanol dropwise over 1.6 hours. After reacting for 5 hours, stop heating to obtain the copolymer.

[0113] (3) Add sodium hydroxide solution to the copolymer to adjust the pH to 5.2, and dilute with water to a mass fraction of 24% to obtain polycarboxylate superplasticizer.

[0114] Comparative Example 6

[0115] The difference between this comparative example and Example 1 is that the polycarboxylate superplasticizer is a commercially available product, purchased from Henan Mingzhixin Chemical Products Co., Ltd.

[0116] Performance testing

[0117] The performance of the UHPC lightweight sheets prepared based on limestone manufactured sand in Examples 1-2 and Comparative Examples 1-6 was tested.

[0118] 1. Compressive strength and flexural strength were tested according to GB / T31387-2015;

[0119] 2. The impact resistance test was carried out in accordance with GBT17657-2013. (1) The test was carried out at room temperature, and the surface of the specimen was observed to see if cracks appeared. (2) The plate was placed at -10℃, 25℃ and 40℃ for 10 days in sequence as a cycle. After three cycles, the impact resistance test was carried out, and the surface of the specimen was observed to see if cracks appeared.

[0120] 3. Durability: Chloride ion flux test and chloride ion penetration resistance study were conducted in accordance with GB / T50082-2009.

[0121] The test results are shown in Table 1.

[0122] Table 1 Performance Test Results

[0123]

[0124]

[0125] As can be seen from the above performance test results, the overall performance of Examples 1-2 is better, especially the overall performance of Example 1 is the most outstanding, which is mainly due to the synergistic effect between the components.

[0126] The comparative examples, lacking the necessary technical solutions, showed significantly inferior performance compared to the exemplary examples in relevant tests. In Comparative Example 1, altered additions of modified ferromanganese slag and modified phosphorus slag powder resulted in decreased compressive strength and chloride ion penetration resistance of the boards. Similarly, in Comparative Example 2, altered additions of fly ash, mineral powder, and limestone manufactured sand led to decreased chloride ion penetration resistance, indicating that the raw material composition of the boards affects chloride ion penetration resistance. Changes in the preparation methods of the polycarboxylate superplasticizer in Comparative Examples 3-5 resulted in decreased temperature resistance and flexural strength of the boards. Comparative Example 6, using commercially available polycarboxylate superplasticizer, exhibited overall inferior performance compared to the products prepared in Examples 1-2. These experimental results further demonstrate the importance of the technical solutions defined in this invention for its technical effectiveness.

[0127] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A lightweight UHPC sheet material prepared based on limestone manufactured sand, characterized in that, The raw materials include the following parts by weight: 22-27 parts ceramsite, 12-15 parts steel fiber, 420-460 parts ordinary cement, 40-50 parts modified ferromanganese slag, 15-27 parts modified phosphorus slag powder, 50-70 parts limestone granules, 10-18 parts steel slag, 20-40 parts fly ash, 40-60 parts mineral powder, 400-420 parts manufactured limestone sand, 6-10 parts polycarboxylate superplasticizer, 0.2-0.4 parts hydroxyethyl methyl cellulose, and 150-170 parts water. The preparation method of modified ferromanganese slag includes: mixing 100 parts by weight of ferromanganese slag powder with 0.2-0.4 parts by weight of tartrate and 0.1-0.3 parts by weight of sodium p-aminobenzenesulfonate to obtain modified ferromanganese slag powder. The method for preparing the ceramsite includes the following steps: (1) Preparation of materials: crush, grind and screen the coal gangue to obtain coal gangue powder with a particle size of 0.1-0.15mm; (2) Mixing: Weigh the raw materials according to the following weight ratio: 12-15% clay powder, 7-12% shale powder, 2-5% mineral powder, and the remainder coal gangue powder; mix the raw materials evenly to obtain a mixed powder; add 20-24% of the total weight of the mixed powder to the mixed powder, stir, and let stand to obtain the mixed powder; (3) Granulation: The mixture is extruded into strips, then dried, crushed and passed through a 100-mesh sieve to obtain dried granules; (4) Calcination: The dried particles are calcined at 1050-1100℃ for 35-40 minutes and then naturally cooled to room temperature to obtain ceramsite. The preparation method of modified phosphorus slag powder includes: mixing 100 parts by weight of phosphorus slag powder, 0.3-0.6 parts by weight of quaternary ammonium salt cationic starch and 0.2-0.4 parts by weight of sodium citrate evenly to obtain modified phosphorus slag powder.

2. The UHPC lightweight sheet material prepared based on limestone manufactured sand according to claim 1, characterized in that, The ordinary cement is a mixture of P.O42.5 ordinary silicate cement and P.O52.5 ordinary silicate cement in a weight ratio of (2-4):

1.

3. The UHPC lightweight sheet material prepared based on limestone manufactured sand according to claim 1, characterized in that, The preparation method of the polycarboxylate superplasticizer includes: (1) Mix 70-80 parts by weight of microcrystalline cellulose and 20-30 parts by weight of unsaturated monomer, treat with microwave assistance, add 1-3 parts by weight of p-toluenesulfonic acid and 0.03-0.05 parts by weight of hydroquinone, stir and heat to 80-100℃ for 5-8 hours to obtain the first monomer; (2) Add 30-40 parts by weight of silane coupling agent KH550 dropwise to 60-70 parts by weight of unsaturated carboxylic acid, add 1-3 parts by weight of p-toluenesulfonic acid and 0.03-0.05 parts by weight of hydroquinone, react at 60-70℃ for 2-3 hours to obtain the second monomer; (3) Mix 30-40 parts by weight of the first monomer, 60-70 parts by weight of the second monomer and 200-250 parts by weight of water, heat to 60-80℃, and add 15-20 parts by weight of maleic anhydride, 1-2 parts by weight of ammonium persulfate and 1-2 parts by weight of isopropanol dropwise over 1-2 hours. After reacting for 2-7 hours, stop heating to obtain the copolymer. (4) Add sodium hydroxide solution to the copolymer to adjust the pH to 5-5.5, and dilute with water to a mass fraction of 22-26% to obtain polycarboxylate superplasticizer.

4. The UHPC lightweight sheet material prepared based on limestone manufactured sand according to claim 3, characterized in that, The unsaturated monomers are a mixture of methacrylic acid, acrylic acid and maleic anhydride in a weight ratio of 1:(1.3-1.7):(0.2-0.5).

5. The UHPC lightweight sheet material prepared based on limestone manufactured sand according to claim 3, characterized in that, The unsaturated carboxylic acids are methacrylic acid, acrylic acid and maleic acid in a weight ratio of (1.6-1.8):1:(0.4-0.7).

6. The UHPC lightweight sheet material prepared based on limestone manufactured sand according to claim 1, characterized in that, Hydroxyethyl methylcellulose is EASONZELL™ ME4000.

7. The UHPC lightweight sheet material prepared based on limestone manufactured sand according to claim 1, characterized in that, The manufactured limestone sand includes 20-40 mesh, 40-70 mesh, and 100-130 mesh manufactured limestone sand in a weight ratio of 1:3-4:0.2-0.

5.

8. The UHPC lightweight sheet material prepared based on limestone manufactured sand according to claim 1, characterized in that, The specific surface area of ​​the mineral powder is 680-770 m². 2 / kg.

9. A method for preparing UHPC lightweight panels based on limestone manufactured sand according to any one of claims 1-8, characterized in that: The preparation method includes the following steps: (1) Weigh the raw materials according to the weight ratio, mix them evenly, and inject them into the mold for vibration molding; (2) Place the molded board in a flat, quiet resting area and let it stand for 4-6 hours for initial setting. The temperature of the initial setting room should be controlled at 18-25℃ and the relative humidity at 65-75%. (3) After the initial curing is completed, the mold is removed and moved to the final curing chamber for steam curing. The temperature of the final curing chamber is controlled at 75-85℃ and the curing time is 45-55h. (4) After the final curing is completed, the material is removed from the final curing room and cured by watering for 17-20 days to obtain UHPC lightweight boards based on limestone manufactured sand.

Citation Information

Patent Citations

  • UHPC (Ultra High Performance Concrete) board prepared from construction waste and preparation method of UHPC board

    CN115611576A

  • UHPC concrete and preparation method thereof

    CN118239740A